2010
DOI: 10.4103/0972-3919.72686
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of effective half life of clearance of radioactive Iodine ( 131 I) in patients treated for hyperthyroidism and carcinoma thyroid

Abstract: BackgroundIn medical applications of radioisotopes, for calculations of whole body doses and radiation safety applications, there is a need to estimate radioactive body burden. Local recommendations in Oman stipulate the need for hospitalization of patients treated for radioactive-iodine (131 I) with activities above 400 MBq.Materials & Methods:A study of body burden estimation from sequentially measured exposure rates from patients treated for carcinoma thyroid and hyperthyroidism was undertaken. A digital au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 3 publications
3
25
1
1
Order By: Relevance
“…Second, whole-body scintigraphy for response assessment is associated with low radiation exposure and currently in our clinic done almost exclusively with rhTSH. Table 7 compiles publications comparing the effect of hypothyroidism and rhTSH on whole-body dose, half-life, or residence time (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most publications are based on studies with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, whole-body scintigraphy for response assessment is associated with low radiation exposure and currently in our clinic done almost exclusively with rhTSH. Table 7 compiles publications comparing the effect of hypothyroidism and rhTSH on whole-body dose, half-life, or residence time (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most publications are based on studies with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report lower whole-body radiation exposure in the rhTSH versus hypothyroid group (6)(7)(8)(9)(10)(11)(12)(13)(14). Comparison of these publications reveals considerable differences in methodology, especially in the methods for measuring thyroid uptake and effective half-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical resection of the thyroid gland followed by 131 I therapy has long been the standard treatment for differentiated thyroid cancer. The 131 I T eff in total body of the patients with intact thyroid gland is generally estimated as 5.5 d (132 h), but in thyroidectomized patients this value is much shorter (Ravichandran et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Barrington et al (1996) with 86 patients, a bi-exponential pattern was found and the correspondent values for T eff in the first and second phase were 0.50 (± 0.09) and 4.28 (± 1.55) days, respectively. In the study by Ravichandran et al (2010), the reported values were 14.4 and 22.0 hours, respectively. The results from the present work, i.e.…”
Section: June 2014mentioning
confidence: 91%